Diversifying Other New Normal Approach on Livelihood Development: Extension Strategies for Poverty Alleviation - Montenegro, Donald (EkBis: Jurnal Ekonomi dan Bisnis, 2025)
This study evaluates and analyzes the extension projects required in Barangay La Paz, Bayabas, Surigao del Sur, to align effectively with the extension agenda of Northeastern Mindanao State University (NEMSU). The research focused on establishing a set of priority projects aimed at supporting poverty alleviation and improving community living standards. Utilizing a descriptive quantitative approach, data were collected from 146 respondents through a rigorously validated and reliable research instrument over a six-month period. The study posits that a transition toward a market-driven extension system is essential to increase community income, stimulate rural entrepreneurship, and create employment opportunities. The results indicate a strong demand for both soft and hard skills training among the community, highlighting a need for formal education in entrepreneurship and livelihood activities. These findings underscore the potential of the University’s extension program to foster sustainable socio-economic development by addressing community-specific needs. The insights from this study inform local legislative and university planning, providing a strategic foundation for selecting extension projects with the highest relevance and impact on beneficiaries.